Karakteristik Penyakit Serebrovaskular Akut Pada Pasien COVID-19 Di Rumah Sakit Mardi Rahayu Kudus - Kristiawan, Ivan Agusta Dwi; Lie, Milka Ardena Lianto; Yudiarto, Fenny Lanawati (Majalah Kedokteran Indonesia, 2022)
Introduction: Several studies have reported that in patients with Coronavirus Disease 2019 (COVID-19), in addition to manifesting abnormalities in the respiratory tract, it can also cause several neurological manifestations, including acute cerebrovascular disease. Acute cerebrovascular disease in COVID-19 is associated with worse manifestation and outcome; therefore, this study wanted to describe the characteristic of acute cerebrovascular disease in COVID-19 patients. The study aims to describe the characteristic of acute cerebrovascular disease in COVID-19 patients.Method: This study was a retrospective observational single-centre study by reviewing the electronic or physical medical records of confirmed COVID-19 patients admitted to Mardi Rahayu Hospital, Kudus from 1 March 2020 to 31 March 2021. The extracted data would be analyzed using the χ2 dan Kolmogorov-Smirnov test for categorical variables and the Mann-Whitney test for numerical variables.Result: From 1053 cases of confirmed COVID-19 that were studied, there were 50(4.7%) cases of acute cerebrovascular disease. Acute cerebrovascular disease patients had older age (57.5 (34-78) years vs 52 (1-88) years, p0.02), were more likely to have hypertension (39(78%) vs 357(35.5%), p less than 0.01), diabetes 31 (62%) vs 383 (38.2%), p=0.01), and prior cerebrovascular disease (11(22%) vs 8(0.8%), p=0.028), had more severe clinical manifestation (32(64%) vs 379(37.8%), p less than 0.01), and had worse outcome (22(44%) vs 218(21.7%), p=0.01). Conclusion: We found that cerebrovascular disease in COVID-19 patients had worse outcomes and clinical manifestation; therefore, management of these cases is better done more cautiously.